2017
DOI: 10.1002/1873-3468.12785
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rab5 isoforms by transcriptional and post‐transcriptional mechanisms in yeast

Abstract: Rab5 GTPases are master regulators of early endosome biogenesis and transport. The genome of Saccharomyces cerevisiae encodes three Rab5 proteins: Vps21, the major isoform, Ypt52 and Ypt53. Here, we show that Vps21 is the most abundant Rab5 protein and Ypt53 is the least abundant. In stressed cells, Ypt53 levels increase but never exceed that of Vps21. Its induction requires the transcription factors Crz1 and Gis1. In growing cells, the expression of Ypt53 is suppressed by post‐transcriptional mechanisms media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In addition to severe defects in endocytic vesicle trafficking, cells lacking Vps21 also exhibit an obvious defect in growth rate, whereas cells lacking either Ypt52 or Ypt53 (or both) have much milder phenotypes. Although the relative levels of each of these proteins may contribute to the differential effects observed in their absence [62], these results are also consistent with Vps21 having a role in promoting the function of TORC2, a central growth regulator, distinct from its function in vesicle trafficking. In agreement with that proposal, in our study [45], we observed that in cells devoid of all three Rab5 paralogs TORC2-mediated phosphorylation of Ypk1 could be stimulated by expression of a GTPlocked Vps21 mutant, which (as already mentioned above) is unable to support vesicle trafficking.…”
Section: Implications Of Rab5-dependent Regulation Of Torc2supporting
confidence: 63%
See 1 more Smart Citation
“…In addition to severe defects in endocytic vesicle trafficking, cells lacking Vps21 also exhibit an obvious defect in growth rate, whereas cells lacking either Ypt52 or Ypt53 (or both) have much milder phenotypes. Although the relative levels of each of these proteins may contribute to the differential effects observed in their absence [62], these results are also consistent with Vps21 having a role in promoting the function of TORC2, a central growth regulator, distinct from its function in vesicle trafficking. In agreement with that proposal, in our study [45], we observed that in cells devoid of all three Rab5 paralogs TORC2-mediated phosphorylation of Ypk1 could be stimulated by expression of a GTPlocked Vps21 mutant, which (as already mentioned above) is unable to support vesicle trafficking.…”
Section: Implications Of Rab5-dependent Regulation Of Torc2supporting
confidence: 63%
“…The three yeast Rab5 GTPases (Vps21/Ypt51, Ypt52, and Ypt53) [62] are involved at an early stage of the endocytic pathway and, akin to their mammalian Rab5 counterparts [63,64], are therefore located primarly on intracellular endosomal vesicles prior to their fusion and delivery to the multivesicular body [65][66][67]. Correspondingly, fluorescently-tagged derivatives of the three yeast Rab5 members exhibit punctate staining on vesicular structures within the cell that co-localize with well-documented endocytic cargo [68,69].…”
Section: Implications Of Rab5-dependent Regulation Of Torc2mentioning
confidence: 99%
“…As a further test of the conclusion that activated Rab5 promotes TORC2 phosphorylation of Ypk1, we examined the effect of reexpressing in the Rab5-deficient vps21Δ ypt52Δ ypt53Δ triple mutant WT Vps21, Vps21(Q66L) (a GTP hydrolysis-defective mutant [so-called “GTP-locked” variant]), or Vps21(S21L) (a mutant that preferentially binds GDP [so-called “GDP-locked” variant]; Tall et al, 1999; Lo et al, 2011; Plemel et al, 2011). We focused on Vps21 because it is constitutively expressed and the most abundant yeast Rab5 isoform (Schmidt et al, 2017), has been shown to play the major role in endocytic vesicle trafficking (Horazdovsky et al, 1994), and when absent, causes more pronounced phenotypes compared with loss of the other two Rab5 GTPases (Singer-Krüger et al, 1994; Nickerson et al, 2012; Nakatsukasa et al, 2014). We found that, when present as the sole Rab5, WT Vps21 was able to rescue AbA-induced TORC2-phosphorylation of Ypk1 7A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the interaction between Vps21 and Tor2 that we detected by coimmunoprecipitation, we explored the possibility that this association, whether stable or transient, is able to stimulate the catalytic function of TORC2, analogous to the stimulation of mTORC1 activity by Rheb in mammalian cells (Avruch et al, 2009; Yang et al, 2017). In vegetatively growing and unstressed cells, Ypt53 expression is repressed (Schmidt et al, 2017). Therefore, to obtain TORC2 from cells depleted of Rab5 GTPases, we used immuno-isolation with anti-FLAG antibodies from extracts of vps21Δ ypt52Δ mutant cells expressing Avo3-3xFLAG, which we were able to demonstrate also successfully enriched for the Tor2 catalytic subunit of TORC2, which was marked with a 3xHA tag (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RNA isolation, cDNA synthesis, and quantitative RT–PCR analysis were performed as described previously (Schmidt et al , ). RNA was extracted from logarithmically growing cells (40 OD) using the Qiagen RNeasy Mini Kit.…”
Section: Methodsmentioning
confidence: 99%